Efficacy of banana fibre paper for the management of the root-knot nematode, meloidogyne incognita, on potato (Solanum tuberosum) in Kenya - Kamau, D. W.; Waceke, W.; Cortada, L.; Mwaura, O.; Pirzada, T.; Sit, T.L.; Davis, E.; Guenther, D.; Mathew, R.; Pal, L.; Khan, S.; Haukeland, S.; et al. (Walter de Gruyter GmbH, 2024)
Globally, potato (Solanum tuberosum) is a key staple food crop. In Kenya, it is the second most important food crop after maize. Among the various constraints to potato production are plant-parasitic nematodes. In particular, root-knot nematodes (Meloidogyne spp.) are a significant impediment to potato production, suppressing yield and reducing the quality of harvested tubers. The current study was undertaken to evaluate the efficacy of a lignocellulose fibre matrix (banana paper) either impregnated with a chemical or drenched with a biologically based nematicide for the management of root-knot nematodes on potatoes, in Kenya. The experiment was conducted in both field and pot trials over two consecutive cropping seasons. Wrapping seed potatoes in banana paper impregnated with abamectin or drenched with Trichoderma asperellum (Real Trichoderma®) led to suppression of soil Meloidogyne incognita densities by 87% and 68% in the field, and 86% and 40% in pots, respectively, which led to a 3.3- and 3.7-fold increase in yield in the field. This novel technology, also referred to as ‘Wrap & Plant’, presents a practical option for nematode management in potato under the resource-limited conditions of sub-Saharan Africa and offers potential for the targeted management of other soil-borne diseases.